Gnome and Rat - Stohler, Lauren; Alfred A. Knopf, Inc.; Random House Children's Books (New York Alfred A. Knopf, 2023)
Best friends Gnome and Rat celebrate Hat Day, learn magic tricks, and find Gnome a new signature hat in their charming forest.
Hat Day -- Gnome fits in a hat -- Gnome grows new hair -- Gnome's new hat -- Back hat it again.
Volume information from spine.
Ages 6-9.
Grades 2-3.
113402
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Gnomes -- Juvenile fiction; Rats -- Juvenile fiction; Hats -- Comic books, strips, etc; Graphic novels; Juvenile works; Fiction; Comics (Graphic works); Graphic novels; Humorous comics